2020
DOI: 10.1080/13880209.2020.1725581
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of different compatibility proportions of the couplet medicines for Astragali Radix andAngelica sinensisRadix on myocardial infarction injury

Abstract: Context: Astragali Radix (AR) and Angelica sinensis Radix (ASR) combinations are used to treat cardiovascular disorders. Objectives: This study investigates the protective effects of different compatibility proportions of AR and ASR on cardiac dysfunction in a C57BL/6 mouse model of myocardial infarction (MI). Materials and methods: MI mice were induced by ligation of the left coronary artery and divided into six groups: sham, vehicle, 10 mg/kg/d simvastatin and combinations of AR and ASR at different ratios, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Ferulic acid (FA) (4-hydroxy-3-methoxy cinnamic acid) is the core active component in Angelica sinensis, which possesses three spiral structures, and is also largely found in several fruits and vegetables. In recent years, FA exhibits an extensive therapeutic impact, such as oxidation resistance, antiageing, anti-inflammation, insulin resistance, and neuroprotective [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic acid (FA) (4-hydroxy-3-methoxy cinnamic acid) is the core active component in Angelica sinensis, which possesses three spiral structures, and is also largely found in several fruits and vegetables. In recent years, FA exhibits an extensive therapeutic impact, such as oxidation resistance, antiageing, anti-inflammation, insulin resistance, and neuroprotective [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Radix Astragali has numerous cardioprotective effects, including reducing in ammatory factor injury and myocardial apoptosis, promoting cardiac microvessel formation and relieving excessive oxidative stress [15][16][17][18]. A recent study showed that the combination of Radix Astragali and Angelica Sinensis not only promoted angiogenesis but also suppressed in ammation and cardiomyocyte apoptosis in a mouse model of MI [19]. The traditional Chinese herb Epimedium has the properties of warming Yang and has been used for the remedy of cardiovascular disease as it has anti-heart failure effect.…”
Section: Discussionmentioning
confidence: 99%
“…These extracts and compounds have a broad range of pharmacological activities, such as hemopoietic, immunoregulatory, anti-inflammatory, antibacterial, antiviral, antioxidant, and antitumor activities. [10][11][12][13] However, the primary effective substances of SYD against CIM and their regulatory mechanisms remain to be explored.…”
Section: Introductionmentioning
confidence: 99%